The European Medicines Agency Review of Ofatumumab (Arzerra®) for the Treatment of Chronic Lymphocytic Leukemia in Patients Refractory to Fludarabine and Alemtuzumab: Summary of the Scientific Assessment of the European Medicines Agency Committee for Medicinal Products for Human Use - Gravanis, Iordanis (AlphaMed Press, 2010)
On April 19, 2010, the European Commission issued a conditional marketing authorization valid throughout the European Union (EU) for ofatumumab (Arzerra®; Glaxo Group Ltd, Greenford, Middlesex, U.K.). The decision was based on the favorable opinion of the Committee for Medicinal Products for Human Use recommending a conditional marketing authorization for ofatumumab for the treatment of chronic lymphocytic leukemia (CLL) in patients refractory to fludarabine and alemtuzumab. A conditional marketing authorization means that additional data to confirm the benefit–risk balance of ofatumumab are awaited. The active substance of Arzerra® is ofatumumab, a monoclonal antibody medicinal product (ATC code L01XC10). The recommended dose is 300 mg of atumumab for the first infusion and 2,000 mg of atumumab for all subsequent infusions. The infusion schedule is eight consecutive weekly infusions, followed 4–5 weeks later by four consecutive monthly (i.e., every 4 weeks) infusions. Ofatumumab targets CD20, a cell surface marker of B lymphocytes, which is followed by cell lysis via complement-dependent cytotoxicity and antibody-dependent cell-mediated cytotoxicity. The benefit of ofatumumab is the control of CLL in patients who are refractory to both fludarabine and alemtuzumab, which was indicated by a high response rate. The most common side effects are infections and infusion reactions. The objective of this paper is to summarize the scientific review of the application leading to approval in the EU. The detailed scientific assessment report and product information, including the summary of product characteristics, are available on the EMA website (http://www.ema.europa.eu).